2020
DOI: 10.17744/mehc.42.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Withdrawal Symptoms Among American Collegiate Internet Gamers

Abstract: We examined the gaming patterns and withdrawal symptomology of 144 American collegiate internet gamers. Our findings indicated that Internet Gaming Disorder Scale (IGDS) scores positively correlated with withdrawal symptomology. The 10 most endorsed withdrawal symptoms were craving to game, impatience, increased sleeping, increased eating, lack of pleasure, irritable/angry, anxious/tense, restless, difficulty concentrating, and increased dreaming. Only 27.1% of gamers did not endorse any withdrawal symptoms. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…The withdrawal symptoms associated with IGD are concerning for college students, who may already be experiencing vulnerability from navigating stress associated with financial strain (Beiter et al, 2015) and exploring new roles and responsibilities (Dyson & Renk, 2006). Furthermore, Giordano et al (2020) found that the more diagnostic criteria that gamers endorsed, the more significant withdrawal symptoms they experienced, indicating that gamers experienced both physiological and emotional characteristics of withdrawal. However, one noted limitation of their study was not identifying the duration of withdrawal symptoms.…”
Section: Igd and Withdrawalmentioning
confidence: 99%
See 3 more Smart Citations
“…The withdrawal symptoms associated with IGD are concerning for college students, who may already be experiencing vulnerability from navigating stress associated with financial strain (Beiter et al, 2015) and exploring new roles and responsibilities (Dyson & Renk, 2006). Furthermore, Giordano et al (2020) found that the more diagnostic criteria that gamers endorsed, the more significant withdrawal symptoms they experienced, indicating that gamers experienced both physiological and emotional characteristics of withdrawal. However, one noted limitation of their study was not identifying the duration of withdrawal symptoms.…”
Section: Igd and Withdrawalmentioning
confidence: 99%
“…However, psychological withdrawal symptoms remain controversial among behavioral-related addictions; therefore, Kaptsis et al (2016) urged for more research on the physical symptoms of withdrawal among those who meet the criteria for IGD. Giordano et al (2020) identified that, during times of abstinence, gamers experienced symptoms consistent with withdrawal, including increases in appetite, sleep, and dreams. Affective symptoms of withdrawal were also reported, including lack of pleasure in previously enjoyable activities, irritability, impatience, anxiousness, restlessness, and difficulty concentrating (Giordano et al, 2020;Kaptsis et al, 2016).…”
Section: Igd and Withdrawalmentioning
confidence: 99%
See 2 more Smart Citations
“…As with all addictions, it is important for counselors to recognize that the treatment of one addictive behavior may lead to the development of a new addictive behavior. Indeed, in the study of 144 collegiate gamers, Giordano et al (2020) found that if gaming was unavailable, 50% of participants indicated being slightly to much more likely to engage in sexual activity, 33.1% indicated being slightly to much more likely to drink alcohol, 11.9% indicated being slightly to much more likely to use illicit substances, 8.3% indicated being slightly to much more likely to gamble/bet, and 5.6% indicated being slightly to much more likely to self-injure. Recall that clients with behavioral addictions often rely on the addictive behaviors to change the way that they feel (e.g., emotion regulation).…”
Section: How Do I Treat It?mentioning
confidence: 99%